2014
DOI: 10.1371/journal.pone.0098936
|View full text |Cite
|
Sign up to set email alerts
|

Secreted β3-Integrin Enhances Natural Killer Cell Activity against Acute Myeloid Leukemia Cells

Abstract: Integrins are a large family of heterodimeric proteins that are involved in cell adhesion, migration, and proliferation. Integrin diversity and function is regulated by alternative splicing. Membrane-bound and truncated β3-integrins were shown to be key players in cancer metastasis. However, the immunomodulatory functions of the soluble (s) β3-integrin have not been investigated yet. In this study, we described a novel form of sβ3-integrin in acute myeloid leukaemia (AML) patients. Furthermore, we assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Younis Skaik et al . 31 demonstrated that secreted integrin (sβ3) has a immunomodulatory functions including induces the secretion of pro-inflammatory cytokines in Natural Killer Cells. We speculated sβ3 may be involved in WISP1’s synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Younis Skaik et al . 31 demonstrated that secreted integrin (sβ3) has a immunomodulatory functions including induces the secretion of pro-inflammatory cytokines in Natural Killer Cells. We speculated sβ3 may be involved in WISP1’s synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is an important mechanism to increase the functional diversity of integrins, and a soluble β3 (sβ3) variant has been detected in the serum for a subset of AML patients [ 72 ]. This variant represents an alternatively spliced and truncated variant.…”
Section: The Soluble Isoform Of β3 Integrinsmentioning
confidence: 99%
“…There has been debate about the involvement of the host stroma and a diversity of non-tumor cell populations in tumor progression 76 . In this context, several mechanisms can contribute synergistically, such as molecules that change the pattern of gene expression in the tumor 77 or being improperly secreted 78 , 79 , as well as heterotypic cell interactions 80 mediated by mediators such as growth factors 81 , cytokines 82 , exosomes 83 and others 84 , that contributes for maintenance of immunosuppressive microenvironment, pro-tumor, with high potential to be refractory to conventional therapies 85 . When analyzing the images of the cases in our cohort, we noticed the immunostaining of both Maspin in regions corresponding to the stroma.…”
Section: Discussionmentioning
confidence: 99%